2017
DOI: 10.1016/j.plefa.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inflammation-resolving lipid mediators RvD1 and DHA are decreased in patients with acutely symptomatic carotid disease

Abstract: Background Efficient biomarkers for early prediction and diagnosis of an acutely symptomatic carotid plaque rupture event are currently lacking, impairing the ability to diagnose and treat patients with an acute plaque rupture events in a timely fashion. Resolvins are endogenous inflammation-resolving lipid mediators that are induced by inflammatory insults. We hypothesized that resolvin and other lipid profiles in sera likely mark the process towards plaque rupture. Methods Circulating lipids associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…Modifications of PUFAs by enzyme oxidation or auto-oxidation can alter the physical properties of neuronal membranes, generate inflammatory mediators, or pro-resolving antiinflammatory mediators (Qu et al, 2015;Bazan et al, 2017;Poreba et al, 2017). Auto-oxidation forms isoprostanes that are indicators of oxidative stress and are neurotoxic.…”
Section: Pufa Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Modifications of PUFAs by enzyme oxidation or auto-oxidation can alter the physical properties of neuronal membranes, generate inflammatory mediators, or pro-resolving antiinflammatory mediators (Qu et al, 2015;Bazan et al, 2017;Poreba et al, 2017). Auto-oxidation forms isoprostanes that are indicators of oxidative stress and are neurotoxic.…”
Section: Pufa Inflammation and Oxidative Stressmentioning
confidence: 99%
“…In early studies, we identified that circulating levels of the SPM 15-epi-lipoxin A 4 (15-epi-LXA 4 ) were significantly lower in individuals with advanced PAD and correlated inversely with disease severity (15). Recent work from other investigators demonstrates that circulating levels of the SPM resolvin D1 (RvD1) or its precursor docosahexaenoic acid (DHA) are reduced in individuals with symptomatic carotid atherosclerosis (33). Thus, an imbalance between proinflammatory and pro-resolving signals may reflect or directly contribute to the progression of atherosclerotic vascular disease in humans (15,20).…”
mentioning
confidence: 99%
“…(13) Moreover, it has been reported that ratios of SPMs to leukotriene B4 (LTB 4 ) are reduced in human vulnerable plaques compared to stable ones. (14) These studies implicate a critical role of resolution and SPMs in T2DM and atherosclerosis. In the present study, we set out to study resolution of in ammation in ox-LDL-challenged macrophages derived from peripheral blood mononuclear cells (PBMCs) of DM patients with AIS ex vivo.…”
Section: Introductionmentioning
confidence: 94%